Flipping theory: Ways in which children’s experiences in the 21st century classroom can provide insight into the theories of Piaget and Vygotsky - Sharkins, Kimberly; Newton, Allison; Causey, Cora; Ernest, James M. (Southeast Asia Early Childhood Journal, 2017)
Although established in the last century, the theories of two well-known psychologists, Jean Piaget and Lev Vygotsky continue to be used throughout the world to prepare teachers and caregivers of young ch ildren(ACEI/Wortham, 2013). From an historical perspective, their theories provide insight regarding children’s growth, development, and learning. Beyond a general understanding however, in what ways do the theories of Piaget and Vygotsky impact 21st century pedagogy, and what might the implementation of those theories look like in today’s classrooms? Observations of children’s experiences in two constructivist oriented classrooms help to provide connections between practice and theory. One classroom draws upon the work of Charlotte Mason, a pioneer of early childhood education in the late 1800’s and early 1900’s and considers the relevance of constructivist education as children examine themselves and develop high moral standards. The second example provides examples of constructivism from a more traditional kindergarten classroom, but one where a teacher uses principals of constructivism to guide developmentally appropriate practices for young children. The purpose of this article is to show how using examples of practice in early childhood classrooms can provide the means for learning about theories of learning and development. Rather than professors using practice to help students understand abstract theory, we flip this pedagogical practice to show how theory can be used with intentional reflection to help teachers understand the practice they